2015
DOI: 10.3906/vet-1212-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the HSPA1A gene by single-strandconformation polymorphism and sequence analysis in Holstein-Friesiancrossbred and Deoni cattle raised in India

Abstract: Materials and methods Experimental animals and DNA isolationDeoni cattle are medium-sized dual-purpose Bos indicus cattle found in parts of the Maharashtra, Karnataka, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although differences in thermo tolerance at the physiological and cellular level have been documented in both Bosindicus and Bostaurus cattle (Collier et al, 2006;Chaiyabutr et al, 2008;W ilson andCrandall, 2010 andDalcin et al, 2016), data on polymorphism of HSP genes in Sahiwal cattle and Holstein Friesian crossbreds is limited. There are only a few reports from India about the relationship of HSP gene polymorphism with heat tolerance in Tharparkar cattle (Bhat et al, 2016), Deoni cattle (Kerekoppa et al, 2015), Jersey crossbred cows (Sailo et al, 2015) and from abroad in Holstein cow (Li et al, 2011). Therefore polymorphisms of HSP90AA1 gene and their association with various physiological, production and reproduction traits in Sahiwal and crossbred cows were investigated in the present study.…”
Section: Introductionmentioning
confidence: 93%
“…Although differences in thermo tolerance at the physiological and cellular level have been documented in both Bosindicus and Bostaurus cattle (Collier et al, 2006;Chaiyabutr et al, 2008;W ilson andCrandall, 2010 andDalcin et al, 2016), data on polymorphism of HSP genes in Sahiwal cattle and Holstein Friesian crossbreds is limited. There are only a few reports from India about the relationship of HSP gene polymorphism with heat tolerance in Tharparkar cattle (Bhat et al, 2016), Deoni cattle (Kerekoppa et al, 2015), Jersey crossbred cows (Sailo et al, 2015) and from abroad in Holstein cow (Li et al, 2011). Therefore polymorphisms of HSP90AA1 gene and their association with various physiological, production and reproduction traits in Sahiwal and crossbred cows were investigated in the present study.…”
Section: Introductionmentioning
confidence: 93%
“…Although differences in thermo tolerance at physiological and cellular level are documented (Collier et al, 2006;Chaiyabutr et al, 2008;W ilson andCrandall, 2010 andDalcin et al, 2016) in both Bos indicus and Bos taurus cattle, information on polymorphism of HSP genes in Sahiwal cattle and Holstein Friesian crossbreds is scarce. There are few reports from India regarding the association of HSP70 and HSP90 gene polymorphism with heat tolerance in Tharparkar cattle (Bhat et al, 2016), Deoni cattle (Kerekoppa et al, 2015), Jersey crossbred cows (Sailo et al, 2015) and from abroad in Holstein cow (Li et al, 2011). Therefore in the present study, polymorphisms of HSP70 and their correlation with various physiological, production and reproduction traits in Sahiwal and crossbred cows were explored.…”
Section: Introductionmentioning
confidence: 95%
“…HSP70 is classified into subfamilies based on minor structural changes in its nucleotide bases, including HSPA1A, HSPA1B, and HSPA1L. The HSPA1A gene subfamily was also associated with cattle performance (Cochran et al, 2013;Kerekoppa et al, 2015;Öner et al, 2017). Suhendro et al (2021) found a base mutation of thymine to guanine in the HSPA1A gene at 5' untranslated region (5'UTR) of transcription position -69 (g.-69T>G).…”
Section: Introductionmentioning
confidence: 99%